The effect of unstable modified wall squat on dynamic balance among recreational badminton players - Chu, Sin Jiet (2022)
Badminton players require a lot of footwork and quickness in changing direction while playing badminton. In order to achieve peak performance, dynamic balance is important for recreational badminton players. Previous research showed that squat is considered as one of the strengthening exercise for lower limb muscles which helps to improve dynamic balance. With the improvement of dynamic balance of a recreational player, risk of getting injury can be reduced. Therefore, the objective of this study is to compare the effect between stable and unstable modified wall squat on dynamic balance among recreational badminton players. This is a randomized controlled trial (RCT) experiment study. The sampling method used in the study was convenience sampling and the sample size was calculated to be at 40 participants with 10% drop off rate by using G*power 3.1 software. 40 participants who met the inclusion criteria and voluntary participate in this study were randomly assigned into control and experimental group, 20 participants in a group. Participants in control group performed stable modified wall squat whereas participants in experimental group performed unstable modified wall squat. Star Excursion Balance Test (SEBT) was used as the pre- and post-test to measure the dynamic balance of all the participants. Pre-test was done on first week whereas the post-test was done on sixth week. There were three sessions per week, lasted for 6 weeks. The data collected were then analyzed by using Paired Sample T Test in IBM SPSS software statistics version 26. There are 40 participants with the age range 18 to 23 years old participated in this research. In the control group, there are 16 males and 4 females with the mean age of 20.40±1.27. In experimental group, there are 12 males and 8 females. The mean weight and height of the participants in control group are 66.27±17.07kg and 172.95±5.94cm respectively whereas the mean weight and height of the participants in experimental group are 59.00±10.08kg and 168.30±7.98cm respectively. The normality test showed that all the data collected are normally distributed. According to the paired sample T test, it showed significant difference on the effect of unstable modified wall squat on dynamic balance among recreational badminton players (p0.05). According to the independent T test, it showed that there is significant difference on effect between both groups on dynamic balance among recreational badminton players (p <0.05). The hypothesis of the study is supported. Through this study, there is no significant effect of stable modified wall squat on dynamic balance among recreational badminton players. But, there is significant effect of stable modified wall squat on dynamic balance among recreational badminton players. Besides that, there is significant effect between stable and unstable modified wall squat on dynamic balance among recreational badminton players. The hypothesis of this study is accepted.